The ethics of deception: secrecy, transparency and deceit in the origins of modern political thought - Rubio, D (2016)
The purpose of this thesis is to reflect on the importance that deception has had on the efficient functioning of societies and the development of individuals. I attempt to do so by adopting an historical perspective, analysing the development of the notion of lawful deception during the Middle Ages and, mainly, the Early Modern Age through theological and political discourses. The scope of my investigation is pan-European. I examine sources from the major Western territories, but I pay special attention to those produced in the Spanish-Habsburg Empire, which was a major political and cultural entity during this period. My claim is that between the thirteenth and seventeenth centuries, the West witnessed the formation of what I call an "Ethics of Deception:" a trend of thought that, without challenging the Augustinian prohibition of lying, recognised deception as intrinsic to nature and mankind, thereby justifying its use from moral and political perspectives. I explain how this intellectual process was conducted, fostered by new social realities, and helped by the flourishing of casuistry, tacitism and neostoicism. Furthermore, I argue that the acceptance of deception contributed to the creation of a new view of the world, language and human interaction. A view that is in the very basis of some of the most characteristic features of Baroque art and that opened the door to some of the most transcendental cultural changes of the period, such as the creation of politics governed by reason rather than faith, the secularisation of social behaviour, and the emergence of the notions of individualism, privacy and freedom of thought. For these reasons, I claim that deception played an important role in the shaping of Modernity.